Portrayal of Female Reactions in Diaspora in Jhumpa Lahiri’s the Namesake - Umesh Devi (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
This dissertation is an attempt to study the female reactions in diaspora with special reference to Jhumpa Lahiri’s The Namesake. The Namesake records the everyday life of an Indian immigrant family that went to America after independence. It can be assumed that as an immigrant’s daughter, the novelist is familiar with the problems of immigrants living in America, particularly their norms, values, culture, religion, language, and above all, their identity. This paper is an analysis of the effects of the diaspora faced by the characters in The Namesake.